2021
DOI: 10.1016/j.amsu.2021.102301
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies levels and potential effects on in-vitro fertilization in a large cohort of infertile Syrian women

Abstract: Background Obstetric morbidities represent a common hallmark manifestation of antiphospholipid syndrome (APS), with the recurrent loss of pregnancy as the main complication. The presence of antiphospholipid antibodies (APA) and its potential impact have not been established yet in infertile women seeking assisted reproduction technologies in Syria. This study aims to determine the prevalence of anticardiolipin antibodies (aCL) and lupus anticoagulation (LAC) and their association with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…Thus, we tried to explore the situation. Results showed that, APA was positive among 20.8% of studied females which higher than reported incidence in literature (0 to 17%) (6,11,12) . Miscarriage was significantly increased among those with positive APA than females with negative APA.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Thus, we tried to explore the situation. Results showed that, APA was positive among 20.8% of studied females which higher than reported incidence in literature (0 to 17%) (6,11,12) . Miscarriage was significantly increased among those with positive APA than females with negative APA.…”
Section: Discussioncontrasting
confidence: 50%
“…But they did not report any effects on the ICSI cycles outcome. The very low percentages of positive APA in Deeb et al (12) study may explain absent association between IVF outcome and presence of APA. The different inclusion criteria could explain the contradiction with the study of Hong et al (6) , as they included females with different autoimmune antibodies other than APA (the sole one in the current work).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Fourth, VDD is associated with a rise in APA in patients with RSA 34 . And RSA is one of the important complications of antiphospholipid syndrome (APS) which caused by cytokine overreaction such as APA and ANA 40,41 . Therefore, we speculate that VDD can cause RSA occurrence by increasing the level of autoimmunity.…”
Section: Discussionmentioning
confidence: 92%
“…34 And RSA is one of the important complications of antiphospholipid syndrome (APS) which caused by cytokine overreaction such as APA and ANA. 40,41 Therefore, we speculate that VDD can cause RSA occurrence by increasing the level of autoimmunity. Fifth, the study found that VDD is correlated with the development of autoimmune thyroid disease (AITD).…”
Section: Discussionmentioning
confidence: 95%